The Arithmetic Sequences in Making Traditional Cast Nets in Lombok - Akbar, Lalu Ajimuliardi; Alghar, Muhammad Zia; Marhayati, Marhayati; Susanti, Elly (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2023)
Mathematical concepts can be found in the culture of the community, such as in daily activities and handicrafts. One type of handicraft is the pencar, a cast net (throw net) fishermen use to catch fish. This research aims to explore the arithmetic sequences involved in making a pencar. This research uses qualitative research with ethnography. The research was conducted in Marong Village, West Nusa Tenggara, Indonesia. Data were obtained by direct observation of the pencar and the process of making it, interviews with cast-net handycrafters, and literature studies on arithmetic sequences. The results of this study show that there are three arithmetic sequences in the pencar. The first sequence, the number of anak (meshes) between each anakan (widener) in the n-th widener row, is 3, 4, 5, and so on, formulated by Un = 3 + (n - 1). The second sequence, the number of anakan (widener) in the n-th widener row is 44, 45, 46, and so on, formulated by Un = 44 + (n - 1). The third sequence, the number of lubang (meshes) in the n-th anakan is 44, 90, 138, 188, and so on, formulated by Un = n^2 + 43n. The arithmetic sequences in pencar can be used as a problem context for culture-based learning in the arithmetic sequence topic.